Kościół męczennika Dionizego w Cyrze (Nebi Houri, Syria) – próba identyfikacji - Nadobnik, Wojciech (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Martyr Dionysius was a local saint worshipped in the area of Cyrrhus in Syria at least since the 4th century. Author of this article combines literary, epigraphic and archeological evidence in order to identify his shrine and estabilsh it’s chronology.